The development of the textbook of basical science concept contained ethnoscience - Kiki Fatkhiyani; Ririn Andriani Kumala Dewi (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2020)
Most textbooks highlight the content of learning material rather than the application of the concept in life, so that only a few students are less aware of the importance of the concept of science to the scientific events or general phenomenon in daily life. There are still a few textbooks that associate the learning material with scientific events or phenomenon that occur in daily life. This research was conducted to develop the textbook of the basic science concepts contained ethnoscience. The formulation of the problem in this research is about how the characteristics and feasibility of the textbook of the basic science concepts contained ethnoscience for PGSD student. The research method used is the RD research method. The research subjects were 22 STKIP NU Indramayu students who took basic science concept of lectures. The instruments used were expert validation sheets and questionnaires. The research plan begins with initial data collection, field studies, making the textbook of basic concepts contained ethnoscience, then proceed with expert validation by the validators using the developed expert validation instrument. After going through the revision of the validators regarding textbook, a trial of the textbook was developed for students by using a questionnaire to find out the user's response to the feasibility of the textbooks of basic science concepts contained ethnoscience. The results of expert validation are 94.5, and it's categorized very validly. Meanwhile, the results of user responses questionnaire are 81.60 with a very decent category.